ANALISIS PENGARUH LABA BERSIH DAN PERUBAHAN PIUTANG TERHADAP ARUS KAS MASA DEPAN PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN - Adam Eprianto; Renil Septiano (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Cash flow statement is a basic financial report that reports cash received, cash paid, and changes therein. Cash flow statements report cash flows in and cash outflows of the company during the period. Cash flow statements are used by management to evaluate ongoing operational activities and plan investment and financing activities in the future. Cash flow reports are also used by creditors and investors in assessing the level of liquidity and the company's potential to generate profits. This study aims to find out and analyze how big the effect of net profit (X1) changes in receivables (X2) on future cash flows (Y) in food and beverage manufacturing companies on the Indonesia Stock Exchange in 2017-2020. The population used in this study were food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange, totaling 32 companies. The analysis technique used was panel data regression. Based on the results of the study (X1) net income has a negative effect on Future cash flows in food and beverage sub-sector manufacturing companies on the Stock Exchange Indonesia, and (X2) changes in receivables have a positive effect on future cash flows in food and beverage sub-sector manufacturing companies on the Indonesian Stock Exchange